2018
DOI: 10.1017/s0305004118000506
|View full text |Cite
|
Sign up to set email alerts
|

On higher energy decompositions and the sum–product phenomenon

Abstract: Let A ⊂ R be finite. We quantitatively improve the Balog-Wooley decomposition, that is A can be partitioned into sets B and C such thatWe use similar decompositions to improve upon various sum-product estimates. For instance, we show |A + A| + |AA| |A| 4/3+5/5277 . The author is partially supported by NSF grant DMS-1501982 and would like to thank KevinFord for financial support. The author also thanks Kevin Ford and Oliver Roche-Newton for useful comments and suggestions, as well as the referee for a meticulou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 33 publications
1
40
0
Order By: Relevance
“…We will use δ 1 to denote the best constant for which we know (1.1) to hold. The current record rests with Shakan [8], who showed that δ 1 = 1/3 + 5/5277 is permissible. Our main result extends the sum-product phenomenon to sets in…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…We will use δ 1 to denote the best constant for which we know (1.1) to hold. The current record rests with Shakan [8], who showed that δ 1 = 1/3 + 5/5277 is permissible. Our main result extends the sum-product phenomenon to sets in…”
Section: Introductionmentioning
confidence: 61%
“…The sumproduct conjecture was first posed by Erdős and Szemerédi in [5]. Since then, numerous authors have worked on estimates of the form (1.1) in the case where A is either a subset of real numbers or some finite field (see [6] and [8]). In recent years, considerable work has also been done to extend these bounds to other rings and fields.…”
Section: Introductionmentioning
confidence: 99%
“…
We show that there exists an absolute constant c > 0, such that, for any finite set A of quaternions, max{|A + A, |AA|} |A| 4/3+c .This generalizes a sum-product bound for real numbers proved progress was made by Konyagin and Shkredov [9], by Rudnev, Shkredov and Stevens [12], and by Shakan [13]. Currently, Shakan's result gives the best bound for δ, showing that Conjecture 1.1 holds with δ ≤ 1/3 + 5/5277, whenever A is a set of real numbers.
…”
mentioning
confidence: 70%
“…(1.4) Many authors have worked on this kind of problem, and in particular, Solymosi [13] proved that one can take δ < 1/3 in (1.4). The current best known bound was given by Shakan [12] which states that δ < 1/3 + 5/5277 is permissible in (1.4).…”
Section: Introductionmentioning
confidence: 99%